2015
DOI: 10.3390/ijerph120605775
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons in the Dagang Oilfield (China): Distribution, Sources, and Risk Assessment

Abstract: The levels of 16 polycyclic aromatic hydrocarbons (PAHs) were investigated in 27 upper layer (0–25 cm) soil samples collected from the Dagang Oilfield (China) in April 2013 to estimate their distribution, possible sources, and potential risks posed. The total concentrations of PAHs (∑PAHs) varied between 103.6 µg·kg−1 and 5872 µg·kg−1, with a mean concentration of 919.8 µg·kg−1; increased concentrations were noted along a gradient from arable desert soil (mean 343.5 µg·kg−1), to oil well areas (mean of 627.3 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…According to the modified standard method [ 15 ], soil samples (10 g dry weight (dw)) and anhydrous sodium sulfate (5 g) were added into a 50 mL glass flask and mixed with 30 mL acetone: dichloromethane solvent (1:1 v / v ). The sample was extracted for 15–20 min in an ultrasonic agitation apparatus (SB 5200 DT, Ningbo Xingzhi Biological Technology Co. Ltd., Ningbo, China), and the final extract was filtered through a column (15 cm length × 10 mm id) filled with 10 cm dried anhydrous sodium sulfate to remove the residual water, and the process was repeated twice again with another 30 mL of solvent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the modified standard method [ 15 ], soil samples (10 g dry weight (dw)) and anhydrous sodium sulfate (5 g) were added into a 50 mL glass flask and mixed with 30 mL acetone: dichloromethane solvent (1:1 v / v ). The sample was extracted for 15–20 min in an ultrasonic agitation apparatus (SB 5200 DT, Ningbo Xingzhi Biological Technology Co. Ltd., Ningbo, China), and the final extract was filtered through a column (15 cm length × 10 mm id) filled with 10 cm dried anhydrous sodium sulfate to remove the residual water, and the process was repeated twice again with another 30 mL of solvent.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular marker approach has been widely used to identify the sources of hydrocarbon compounds [ 13 , 14 ]. However, most studies have been focused on PAH pollution in urban, mine and oil field soils [ 15 , 16 , 17 ], but seldom in chemical plant areas. PAH soil pollution near chemical plants could cause public health risks since residences and parks are nearby [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the presented results are significantly higher compared to other values reported for the top layer of agricultural soils from non-industrial areas in Poland by Oleszczuk and Pranagal (2007), 105-290 μg kg −1 ; Maliszewska-Kordybach et al (2008,2009), 80-7264 μg kg −1 as well as in Japan, 52.9-2810 μg kg −1 (Chen et al 2017); China, 176.1-563.3 μg kg −1 (Lang et al 2015) and 103.6-5872 μg kg − 1 (Jiao et al 2015) and Norway, 9-11,000 μg kg −1 (Nam et al 2008). Our values even exceed the values of other areas subjected to significant anthropogenic pressure, e.g.…”
Section: Compositional Profile and Identification Of Pahs Sourcesmentioning
confidence: 99%
“…Volatilization was expected to drastically reduce the concentration of the low molecular weight PAHs, but if naphthalene was quickest to migrate to the sorption sites of the soil, there would be the tendency of sorption inhibiting its volatilization even though it has the highest vapour pressure among the 16 priority PAHs studied. Other studies have also demonstrated the occurrence of naphthalene in hydrocarbon polluted soil at significant levels [10,11]. This in-turn would mean that the un-adsorbed low molecular weight PAHs would have the tendency to volatilize or migrate to the sub-surface.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the ecological and human health risks of exposure to PAHs due to hydrocarbon pollution in soils and sediments [2,[9][10][11]. However, it is not yet very clear the level of ecological and human health risks associated with PAH soil pollution as encountered from spill incidents arising from the Telecom industry.…”
mentioning
confidence: 99%